2017
DOI: 10.1111/rec.12596
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance and resilience of forest species to frost in restoration planting in southern Brazil

Abstract: Listing potential species for restoring areas has become a complex task considering the lack of information regarding the silvicultural behavior of native trees after planting and their responses to environmental conditions. Frost is an important meteorological phenomenon that regulates the distribution of plant species, especially in subtropical regions. Thus, we evaluated the effect of frost and the resilience potential of native forest species in restoration planting of a riparian forest in southern Brazil.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
(29 reference statements)
0
4
0
3
Order By: Relevance
“…A silvicultura de espécies nativas é uma atividade incipiente no Brasil, quando comparada à de espécies comerciais exóticas (Rorato et al, 2018). No que tange à restauração florestal, restam lacunas relevantes sobre o desempenho de espécies nativas em funções como no controle de espécies exóticas invasoras, na recuperação das propriedades do solo e na atração da fauna (Zahawi et al, 2013).…”
Section: Introductionunclassified
“…A silvicultura de espécies nativas é uma atividade incipiente no Brasil, quando comparada à de espécies comerciais exóticas (Rorato et al, 2018). No que tange à restauração florestal, restam lacunas relevantes sobre o desempenho de espécies nativas em funções como no controle de espécies exóticas invasoras, na recuperação das propriedades do solo e na atração da fauna (Zahawi et al, 2013).…”
Section: Introductionunclassified
“…Frost, depending on the intensity, compromises the development of initial plantings (VANONI et al, 2016;TURCHETTO et al, 2020a). Rorato et al (2018b) reported reduced growth of forest species in a forest restoration plantation in the southern tip of the Atlantic Forest Biome. In the present study, it was found that M. scabrella, A. angustifolia, and C. trichotoma managed to resume their growth after frost events, suggesting a certain tolerance to low temperatures.…”
Section: Discussion Experiments 1: Planting Species In Full Sunmentioning
confidence: 99%
“…Frost can hamper the restoration of plant communities (Snowcroft & Jeffrey, 1999;Snowcroft et al, 2000;Curran, Reid & Skorik, 2010;Rorato et al, 2018). In this study, we calibrate a cold-air pooling (CAP) model to predict where frost may occur in the complex terrain of the sub-escarpment lowlands of South Africa where subtropical thicket is the dominant vegetation.…”
Section: Introductionmentioning
confidence: 99%